Current treatment of pelvic organ prolapse correlated with chronic pelvic pain, bladder and bowel dysfunction. Issue 3 (May 2017) - Liedl, Bernhard; Goeschen, Klaus; Durner, Leopold
Abstract : Purpose of review: The purpose of this review is to critically analyze the relationship between symptoms of abnormal emptying of the bladder, urgency, pelvic pain, anorectal dysfunction and pelvic organ prolapse (POP) and to present evidence in order to show how many of the above mentioned symptoms can be cured or substantially improved by repair of specific pelvic ligaments. Recent findings: In this review, we provide evidence to show how often these dysfunctions occur and how they can be cured in 42–94% by appropriate pelvic floor surgery in the longer term, up to 2 years. Laxity in ligaments and/or vaginal membrane due to damaged connective tissue may prevent the normal opening and closure mechanism of urethra and anus, because muscles need finite lengths to contract properly. Hypermobility of the apex can irritate the pelvic plexus causing chronic pelvic pain. In consequence, dysfunctions as abnormal emptying of the bladder, urgency, pelvic pain, fecal incontinence and obstructed defecation can occur in women with different degrees of POP. Summary: In conclusion, it has to be recognized that women bothered by these symptoms should be examined for POP and appropriately advised for possibility of cure by pelvic floor surgery after careful selection. Video abstract: http://links.lww.com/COU/A9 Abstract : Supplemental Digital Content is available in the text